The chosen pedagogical and ethical aspects in the care of elderly people - Cuber, Tomasz; Dobrowolska, Beata; Kościołek, Aneta; Mianowana, Violetta (Nursing Problems / Problemy Pielęgniarstwa, 2010)
The ongoing demographic changes concerning the increase of human life force specialists of various scientific disciplines, especially social and medical sciences, to reorganised their view of a human being of advanced age. The crucial issues of the contemporary gerontology are addressed on the development of proper attitudes towards the elderly people and fluctuate around: 1) preparation of the young generation for challenges of the old age as every individual faces the entrance into the "third age" world. So, the affirmation of the active and creative ageing phase should become the main goal of gerontology and the work for achieving it should start as early as it is possible; 2) change in young people’s attitude towards the persons of advanced age throughout the appreciation of their life experience, tradition and identity from the older generation. The aim of the paper is to review the contemporary gerontological tendencies which can be used in care of the older patient with consideration of the newest pedagogical concepts and ethical basis in this area. The analysed issues are focused on description of biological and psycho-social theories of ageing which influenced the subjective feeling concerning the quality of life. As a rule together with ageing process the self-reliance of the elderly decreases what is connected with the need of the enhanced care. The level of self-reliance of the people of advanced age depends in great measure on their attitude towards the old age which should be build throughout the entire life. The main aim of health education towards the old age described as long, healthy and active elderly phase of human life and positive attitude was illustrated in the study. Apart from pedagogical indicators of gerontological care the ethical aspects of the elderly were pointed out which are based on the latest British patterns in this scientific field. Nursing Topics 2010; 18 (4): 490-496